2018
DOI: 10.1016/j.parkreldis.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter availability reflects gastrointestinal dysautonomia in early Parkinson disease

Abstract: GI dysautonomia correlates with reductions in DAT availability; constipation is most closely associated with caudate-DAT reduction. Worsening GI-dysautonomia and reduced bowel movements may accompany advancing nigral degeneration or changes in nigrostriatal dopamine function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
7
25
1
Order By: Relevance
“…Our association with gastrointestinal symptoms is in accordance with a previous study that suggested the involvement of striatal D2 receptors in the salivary response through signalling via the globus pallidus and mesencephalic reticular formation to the sympathetic preganglionic neurons in the spinal cord [19]. A recent DaT study also found that gastrointestinal dysfunction, especially constipation, is associated with striatal dopaminergic degeneration [26]. In accordance with our findings, their association was stronger in the caudate nucleus than in the putamen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our association with gastrointestinal symptoms is in accordance with a previous study that suggested the involvement of striatal D2 receptors in the salivary response through signalling via the globus pallidus and mesencephalic reticular formation to the sympathetic preganglionic neurons in the spinal cord [19]. A recent DaT study also found that gastrointestinal dysfunction, especially constipation, is associated with striatal dopaminergic degeneration [26]. In accordance with our findings, their association was stronger in the caudate nucleus than in the putamen.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, to our knowledge, no study has yet investigated the association between the integrity of the serotonergic system and autonomic dysfunction in PD using nuclear imaging. Recent studies have shown relationships between constipation [26] and urinary symptoms [27] and reduced striatal DAT availability, but more research is needed to confirm these findings. In the current study, [ 123 I]FP-CIT SPECT imaging was used to investigate the relationship between extrastriatal SERT availability, as well as striatal DAT availability, and the severity of autonomic symptoms in PD.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms previous observations from Hinkle et al [31], who described an association between SCOPA-GI score (especially constipation items) and both regions. Additionally, we observed that the SCOPA-URO subscore was also negatively correlated with striatal uptake.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, a significant association was found between SCOPA-GI subscore and caudate/putamen uptake. This confirms previous observations from Hinkle et al [25], who described an association between SCOPA-GI score (especially constipation items) and both regions. Additionally, we observed that the SCOPA-URO subscore was also negatively correlated with striatal uptake.…”
Section: C-pe2i and 11 C-dasbsupporting
confidence: 93%